2003
DOI: 10.1016/s0002-9270(02)06015-x
|View full text |Cite
|
Sign up to set email alerts
|

Fibrosis in chronic hepatitis C acquired in infancy: is it only a matter of time?

Abstract: Chronic hepatitis C acquired in childhood is a progressive, slow-moving, fibrotic disease. Fibrosis progression inferred on the basis of linear mathematical models should be critically evaluated in the clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 18 publications
4
50
1
1
Order By: Relevance
“…In the study by Mohan et al ,62 one of four children with paired biopsies developed early cirrhosis over a 4-year period. Our retrospective data on a small group of children who underwent a second biopsy 3–17 years after their first, showed that 54% of cases had an increase in the fibrosis score, which correlated with a more marked histological activity at the first biopsy and a longer interval between the two biopsies 65. Overall, these data and the observation that none of the children who had been infected for more than 15 years were without fibrosis suggest that the progression of fibrosis is time-dependent, even though it is a slow and non-linear process.…”
Section: Hepatitis C Virus Infectionmentioning
confidence: 86%
“…In the study by Mohan et al ,62 one of four children with paired biopsies developed early cirrhosis over a 4-year period. Our retrospective data on a small group of children who underwent a second biopsy 3–17 years after their first, showed that 54% of cases had an increase in the fibrosis score, which correlated with a more marked histological activity at the first biopsy and a longer interval between the two biopsies 65. Overall, these data and the observation that none of the children who had been infected for more than 15 years were without fibrosis suggest that the progression of fibrosis is time-dependent, even though it is a slow and non-linear process.…”
Section: Hepatitis C Virus Infectionmentioning
confidence: 86%
“…10 34 When the linear model for predicting the progression of hepatic fibrosis was applied to a small series of infants with chronic hepatitis C, the prediction was unreliable in 97% of cases. 35 In an image analysis study aimed at assessing the impact of liver biopsy sampling variability on liver fibrosis evaluation, the increase in fibrous tissue accumulation in hepatitis C was threefold for the early stage F2 samples versus 12-fold for advanced stage F4 samples compared with F0 samples with no fibrosis. 36 In conclusion, this study demonstrates that reactivation is part of the natural course of chronic hepatitis C and that it is closely associated with genotype 2c infection.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of children have chronic asymptomatic hepatitis C (CHC) with minimal histological inflammation and fibrosis 3 4. Nevertheless, by the time they reach adulthood, approximately 5% of children with CHC will have evidence of hepatic fibrosis and cirrhosis 5. Hence, the long-term health and economic impact of paediatric HCV cannot be overemphasised 6…”
Section: Introductionmentioning
confidence: 99%